The Validity of Pop-up Book Media at Changing the Form of Objects Topic - Adnyana, Made Agus Dwi; Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2020)
The results of the analysis of the fifth-grade elementary school students' books in the second-semester Theme 7 and the results of observations in elementary schools state that the manuals used by teachers and students in the learning process are still limited especially in science material. The appearance of the book also less attractive, so students become less understanding of the material explained. In addition, the lack of use and development of media in the teaching and learning process also underlies the implementation of this research. The purpose of this research was to develop a pop-up book media on the topic of changing the form of objects with validity tested. This research was conducted using the ADDIE development model (analyze, design, development, implementation, evaluation). However, due to limited time, resources, and finances, the research was only carried out until the development stage. The subject in this research was the pop-up book media on the topic of changing the form of objects. Whereas the object of this research was the validity of the pop-up book media on the topic of changing objects. The method used in this study was a questionnaire given to two teachers and two lecturers as experts. The instrument used was a rating scale in the form of media assessment sheets for experts. The data analyzed with the mean formula to find out its validity. The average score of the pop-up book media after being reviewed by experts was 4.87 with very good qualifications. The implication of this research was the existence of pop-up book media that have very good qualifications. Based on the results of the analysis, the developed media was valid and can be used by the teacher to facilitate the teacher in explaining the material, especially on the topic of changing the form of objects in the fifth grade of elementary school.